Survey of obesity among school children in rural Kerala, India - Abraham, Robin Joseph; Pillai, Priyadarsini C. (International Journal of Contemporary Pediatrics, 2019)
Background: Childhood obesity is a risk factor for subsequent development of diabetes mellitus, hypertension etc. Rural children show lower levels of obesity and higher rates of malnutrion. Objectives: Study seeks to access the prevalence of obesity and overweight among higher secondary students in rural Kerala). Methods: 1577 students were selected from schools picked randomly in and around vadavukode block in Ernakulam district, Kerala, of which 761 from private and 816 from government and aided school. Their height, weight and BMI was recorded and plotted in WHO growth charts to assess stunting, wasting, overweight and obesity. Results: No difference was found among the government and private schools. The finding from the data tally with the results from other parts of rural India with overweight and obese children (around 10%). The study found 44% children were found to be undernourished. Malnutrition was noted in both private and public schools possible highlighting knowledge deficit on Nutrition may be the cause of malnutrition. Only 47% students were in the normal range. Conclusions: Rural Kerala is afflicted with a serious problem of undernutrition and lower levels of obesity. There was striking prelidiction for obesity was noted among stunted children in the study highlighting the complex nature of the nutrition problem in India where malnutrition and obesity coexist and cause double burden of diseases. The solution is to encourage the message of healthy living, equally to the over nourished and the undernourished, where balanced diet and exercise as a way of life is encouraged.